Mixing tree species at different spatial scales: The effect of alpha, beta and gamma diversity on disturbance impacts under climate change. Issue 8 (3rd June 2021) - Sebald, Julius; Thrippleton, Timothy; Rammer, Werner; Bugmann, Harald; Seidl, Rupert
Abstract: Single species forest systems often suffer from low resistance and resilience to perturbations. Consequently, fostering tree species diversity is discussed as an important management approach to address the impacts of changing climate and disturbance regimes. Yet, the effect of the spatial grain of tree species mixtures remains unknown. We asked whether increasing tree species diversity between stands (beta diversity) has the same effect as increasing tree species diversity within stands (alpha diversity) at similar overall levels of richness (gamma diversity). We conducted a multi‐model simulation experiment under climate change, applying two forest landscape models (iLand and LandClim) across two contrasting landscapes of Central Europe. We analysed the effect of different levels and configurations of diversity on the disturbance impact and the temporal stability of biomass stocks and forest structure. In general, increasing levels of diversity decreased disturbance impacts. Positive diversity effects increased with increasing severity of climate change. Beta diversity buffered disturbance impacts on landscape‐level biomass stocks more strongly than alpha diversity. The effects of the spatial configuration on forest structure were more variable. Diversity effects on temporal stability were less pronounced compared to disturbance impacts, and mixture within and between stands had comparable effects on temporal stability. Diversity effects were context‐dependent, with patterns varying between landscapes and indicators. Furthermore, we found a strong species identity effect, with increasing diversity being particularly beneficial in conifer‐dominated systems of the European Alps. The two models agreed on the effects of different levels and configurations of tree species diversity, underlining the robustness of our findings. Synthesis and application . Enhancing tree species diversity can buffer forest ecosystems against increasing levels of perturbation. Mixing tree species between stands is at least as effective as mixing tree species within stands. Given the managerial advantages of between‐stand mixtures (e.g. reduced need to control competition to maintain diversity, higher timber quality, lower logistic effort), we conclude that forest management should consider enhancing diversity at multiple spatial scales. ​ Abstract : Enhancing tree species diversity can buffer forest ecosystems against increasing levels of perturbation. Mixing tree species between stands is at least as effective as mixing tree species within stands. Given the managerial advantages of between‐stand mixtures (e.g. reduced need to control competition to maintain diversity, higher timber quality, lower logistic effort), we conclude that forest management should consider enhancing diversity at multiple spatial scales. ​